(untitled) - PERRY, GREG (USA, 1994)
1.At a glance / 2.The C++ phenomenon / 3.C++ is superior / 4.Simple I/O / 5.Powerful pointers / 6.Memory allocation: there when you need it / 7.communicating with funtions / 8.Overloaded functions lessen your load / 9.Add some class to your data / 10.Member functions activate class variables / 11.Friends when you need them / 12.Introduction to overloading operators / 13.Extending operator overloads / 14.Constructing and deconstructing / 15.Loose ends: static and larger programs / 16.It's herediraty: Inheriting data / 17.Inhereting limits and extensions / 18.Data composition / 19.Virtual functions: Are they real / 20.Introduction to Throwing and catching exceptions / 21.Easy file I/O / 22.the visual C++ tools / 23.Introduction to Windows programming and MFC / 24.The MFC classes: power you will gain / 25.Files and more MFC / 26.Graphics and visual C++ / 27.What's next
Incluye indice pag.907 / Incluye glosario pag.899 / Incluye apendice pag.787
Keywords: POGRAMACION ORIENTADA A OBJETOS (COMPUTADORES)- VISUAL C++